How to Prepare Leadership and Change Management in the Digital Area (Case Study at Gojek Indonesia) - Tatik Mulyati; Rabhi F. Muhammad; Handaru Agnyana; Nurimansyah Nurimansyah (Pattimura University, 2026)
The expansion of digital technologies has profoundly altered how organizations function, make decisions, and deliver value. As digital transformation becomes a defining characteristic of modern business environments, leaders must be equipped to guide their organizations through continuous change while maintaining stability and effectiveness. This article examines how leadership preparation and structured change management can support organizations in adapting to digital disruption. Using a qualitative synthesis of academic literature and a contextual case study from Gojek Indonesia, the study reviews theories related to digital leadership, organizational readiness, and formal change frameworks. Recent studies highlight that digital leadership and transformation are deeply interlinked, and that leadership behavior strongly shapes organizational agility and innovation capacity. The findings indicate that successful digital transformation depends on leaders’ ability to foster adaptable mindsets, encourage collaboration, and support cultures willing to experiment and learn. Beyond technology deployment, digital change requires clear communication, capacity development, and alignment across all levels of the organization. The implications emphasize the need for strategic leadership development, competency strengthening, and deliberate interventions to ensure long-term resilience in the digital era.